Human Pegivirus Type 1: A Common Human Virus That Is Beneficial in Immune-Mediated Disease? - Stapleton, Jack T. (Frontiers in Immunology, 2022)
Two groups identified a novel human flavivirus in the mid-1990s. One group named the virus hepatitis G virus (HGV) and the other named it GB Virus type C (GBV-C). Sequence analyses found these two isolates to be the same virus, and subsequent studies found that the virus does not cause hepatitis despite sharing genome organization with hepatitis C virus. Although HGV/GBV-C infection is common and may cause persistent infection in humans, the virus does not appear to directly cause any other known disease state. Thus, the virus was renamed “human pegivirus 1” (HPgV-1) for “persistent G” virus. HPgV-1 is found primarily in lymphocytes and not hepatocytes, and several studies found HPgV-1 infection associated with prolonged survival in people living with HIV. Co-infection of human lymphocytes with HPgV-1 and HIV inhibits HIV replication. Although three viral proteins directly inhibit HIV replication in vitro, the major effects of HPgV-1 leading to reduced HIV-related mortality appear to result from a global reduction in immune activation. HPgV-1 specifically interferes with T cell receptor signaling (TCR) by reducing proximal activation of the lymphocyte specific Src kinase LCK. Although TCR signaling is reduced, T cell activation is not abolished and with sufficient stimulus, T cell functions are enabled. Consequently, HPgV-1 is not associated with immune suppression. The HPgV-1 immunomodulatory effects are associated with beneficial outcomes in other diseases including Ebola virus infection and possibly graft-versus-host-disease following stem cell transplantation. Better understanding of HPgV-1 immune escape and mechanisms of inflammation may identify novel therapies for immune-based diseases.